1996
DOI: 10.1021/ja960252t
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Study of the Formation and Dissociation of Fe(CO)4H2:  Kinetics and Bond Dissociation Energies

Abstract: Time-resolved IR spectroscopy has been used to study the oxidative addition of H2 to Fe(CO)4 and its reverse reaction, the reductive elimination of H2 from Fe(CO)4H2, in the gas phase. The rate constant for oxidative addition of H2 shows little temperature dependence, indicating that if there is an activation barrier for this process it is small (<4 kcal mol-1). The activation barrier for the reductive elimination of H2 is 20.5 ± 2.1 kcal mol-1. From these measurements, the average of the dissociation energies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 25 publications
6
46
1
Order By: Relevance
“…All adducts Fe(CO) 4 (L) have singlet ground states. As one might expect, gas phase addition of ligands follows second‐order kinetics, first order in the iron fragment and in ligand . However, in solution, the rate of product formation appears not to depend on ligand concentration .…”
Section: Applicationsmentioning
confidence: 86%
See 1 more Smart Citation
“…All adducts Fe(CO) 4 (L) have singlet ground states. As one might expect, gas phase addition of ligands follows second‐order kinetics, first order in the iron fragment and in ligand . However, in solution, the rate of product formation appears not to depend on ligand concentration .…”
Section: Applicationsmentioning
confidence: 86%
“…An example of more quantitative insight concerns the reactivity of iron tetracarbonyl. This unsaturated fragment, with a triplet ground state, is generated by photolysis of iron pentacarbonyl, and the subsequent kinetics of ligand addition to the fragment have been studied both in the gas phase and in solution . All adducts Fe(CO) 4 (L) have singlet ground states.…”
Section: Applicationsmentioning
confidence: 99%
“…The H 2 oxidative addition to Fe(CO) 4 has been investigated experimentally 16 and theoretically. 28 The experimental study has shown that the reaction rate is three orders of magnitude slower than the H 2 addition to related electronically unsaturated complexes, a phenomenon tentatively attributed to the spin-forbidden character of the process.…”
Section: 35mentioning
confidence: 99%
“…The relatively high energy of the MECPs in all cases suggests that the rate of addition of H 2 to unsaturated fragments FeL 4 should proceed significantly more slowly than the collisional or diffusion rate, and this has indeed been observed experimentally. Gas-phase addition to Fe(CO) 4 (under high-pressure limiting conditions) 16 is ca. three orders of magnitude slower than is typical for addition of H 2 to other coordinatively unsaturated species, and Fe(dmpe) 2 reacts with dihydrogen roughly 7500 times slower than does Ru(dmpe) 2…”
Section: Minimum Energy Crossing Pointsmentioning
confidence: 99%
“…on the gas-phase reactivity of spin triplet Fe(CO) 4 should also be underlined [36][37][38]. We emphasize in this article, however, that spin crossover reactivity is a common phenomenon also for reactions of commonly available organometallic compounds in solution.…”
Section: Spin Crossover Reactions: the Forbiddenness Factormentioning
confidence: 93%